The demands of caregivers of children with acute lymphoblastic leukaemia in different therapy stages and the exploration of possible interventions: A longitudinal investigation survey at a Tertiary Medical Institution. Issue 4 (7th December 2022) - Liu, Yang; Ma, Linyu; Mo, Lin; Shen, Xuelan; Zhong, Dahui
Abstract: Aim: To describe the demands of family caregivers of children with ALL at different therapy stages and explore the possible interventions to address their care demands. Design: A longitudinal investigation study. Method: A total of 157 family caregivers of children treated in the Haematological oncology ward of a tertiary medical hospital in China between March and December in 2020 were included in this study. The Comprehensive Needs of Caregivers of Cancer Patients and Families Taking Care of Children Scale was used to investigate the family caregivers of children with ALL. The family caregivers completed the questionnaire accompanied by a researcher within two weeks of each therapy stage, which included the induction, consolidation and continuation stages. Results: Family caregivers of children with ALL had many demands that varied based on the stage of therapy. Family caregivers in the induction therapy stage needed more information about their children's disease, having the highest score in information demands (35.60 ± 5.85). The family caregivers in the consolidation therapy stage needed more information on symptom management and socio‐economic support, having the highest score in care and support demands (36.14 ± 5.12). The family caregivers in the continuation therapy stage (including interim and maintenance therapy stages) focused more on their own and the children's social adaptation, so they scored the highest for psychosocial demands (35.96 ± 5.69). Conclusion: Family caregivers of children with ALL had different demands that varied based on the stage of therapy. Medical personnel should be aware of the primary needs of family caregivers at different therapy stages to provide early interventions and support based on their demands, ultimately improving the physical and mental condition of family caregivers and the quality of care.